Home » If b3 = a-2 and c(frac{1}{3}) = a(frac{1}{2})b, express c in terms of a

If b3 = a-2 and c(frac{1}{3}) = a(frac{1}{2})b, express c in terms of a

If b3 = a-2 and c(frac{1}{3}) = a(frac{1}{2})b, express c in terms of a
  • A.
    a-(frac{1}{2})
  • B.
    a(frac{1}{3})
  • C.
    a(frac{3}{2})
  • D.
    a(frac{2}{3})
Correct Answer: Option A
Explanation

c(frac{1}{3}) = a(frac{1}{2})b
= a(frac{1}{2})b x a-2
= a-(frac{3}{2})
= (c(frac{1}{3}))3
= (a-(frac{3}{2}))(frac{1}{3})
c = a-(frac{1}{2})

Related:  If x10 = 235. Find x